Educational Outcomes of English Language Learners at University - Roessingh, Hetty; Douglas, Scott (Canadian Journal of Higher Education, 2012)
This study compares the undergraduate academic achievement of domestic English language learners (ELLs) of different age on arrival (AOA) cohorts to native English speakers (NS), all of whom graduated from local high schools. The broad research question that frames the study is how the literacy levels of ELLs of different AOA cohorts influence retention, progress, and grade point average (GPA) as indicators of academic success. Findings suggest that ELLs are resilient and determined as they make progress toward degree status. However, their progress and achievement, regardless of AOA, is fraught with challenges. This outcome represents a loss of educational capital for Canada in an economy that needs the participation of these students, who are among our brightest and best. Suggestions are made for policy reform, pedagogy, and service provision for ELLs at university.